Relationship of variations of the total electron content of ionosphere in magnetically conjugated regions with precipitation of high-energy charged particles - Zanimonskiy, Y. M.; Koloskov, A. V.; Yampolski, Yu. M.; Nykiel, G.; Sopin, A. O.; Zanimonskiy, Y. Y. (Ukrainian Antarctic Journal, 2019)
Purpose. A qualitative and quantitative study of the correlation of space-time changes of the total electron content of the ionosphere with variations in the energetic electron flux during a significant increase of the solar wind density and velocity. Determination of the conditions when the increase of the intensity of the flux of energetic electrons can be accompanied by the appearance of large-scale inhomogeneities of the ionosphere observed in magnetically conjugated regions of the Northern and Southern hemispheres. Methods. The research methodology is based on the construction of the time sequence of electron fluxes spatial distributions and their subsequent comparison with the maps of the total electron content (TEC) over North America and the TEC diurnal variations in magnetically conjugated regions. The degree of similarity has been estimated in this paper, and the corresponding correlation coefficients have been obtained. The TEC was calculated from the ground-based Global Navigation Satellite System (GNSS) observations, and the electron fluxes in the ionosphere were obtained from the in situ measurements by the POES satellites. The map-making region was selected by the presence of a dense network of GNSS receivers and the presence of stations in the magnetically conjugated region of the Antarctica, as well as by the favorable configuration of spatial distribution of energetic particles at the orbital height of POES satellites. The study is based on the two geomagnetic disturbances of the St. Patrick’s Days in March 2013 and 2015. Results. The satellite and ground-based data during geomagnetic disturbances were processed by using the developed technique. It is found that the consistency of changes in the total electron content of the ionosphere and electron fluxes in time and space coincide with the variation range increase of the horizontal component of the geomagnetic field that has been observed according to the data of ground-based magnetometers and indicates the existence of ionospheric currents in the geospace. According to the analysis of the two events, the assumption is made that the presence of ionospheric currents formed by protons and electrons precipitated from the magnetosphere is one of the conditions for the consistency of changes in the total electron content and electron flux. Conclusions. It is shown that during the geomagnetic disturbances the space-time changes of the ionospheric inhomogeneities are partially consistent with the variations of the fluxes of energetic electrons that allows the possibility of using these observations of TEC as indicators of precipitation.